2017
DOI: 10.21037/acs.2017.05.12
|View full text |Cite
|
Sign up to set email alerts
|

Isolated septal myectomy for hypertrophic obstructive cardiomyopathy: an update on the Toronto General Hospital experience

Abstract: Background: Isolated septal myectomy is considered the gold standard for refractory left ventricular outflow tract (LVOT) obstruction at centers with dedicated hypertrophic obstructive cardiomyopathy (HOCM) surgeons. In this paper, we provide an update on the Toronto General Hospital (TGH) experience for isolated septal myectomy and comment on the safety and efficacy of myectomy in patients with thin basal septal thickness at our institution. Methods:We retrospectively reviewed all patients undergoing surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 21 publications
(19 reference statements)
0
31
0
2
Order By: Relevance
“…A study by Vanderlaan et al has shown a complete depletion of SAM, but the proportion of patients with preoperative SAM was lower (50%) than in our study (76%). 18 It has been unclear whether SAM at rest persists during exercise or whether SAM may reappear during exercise. In this study, SAM at rest persisted during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Vanderlaan et al has shown a complete depletion of SAM, but the proportion of patients with preoperative SAM was lower (50%) than in our study (76%). 18 It has been unclear whether SAM at rest persists during exercise or whether SAM may reappear during exercise. In this study, SAM at rest persisted during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Surgical myectomy has demonstrated excellent long-term efficacy and safety at selected high-volume centres with near-complete resolution of resting and inducible LVOT gradients, perioperative mortality rates <1%, and long-term survival similar to demographic-matched controls. 68,69 Nonetheless, it remains a major operation with risks that may be prohibitive or undesirable for certain patients. Moreover, outcomes have been substantially less impressive outside of experienced centres, with an overall mortality of 5.2% in a nationally representative US database.…”
Section: Novel Procedural Techniques For Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Surgical myectomy has demonstrated excellent long‐term efficacy and safety at selected high‐volume centres with near‐complete resolution of resting and inducible LVOT gradients, perioperative mortality rates <1%, and long‐term survival similar to demographic‐matched controls . Nonetheless, it remains a major operation with risks that may be prohibitive or undesirable for certain patients.…”
Section: Novel Procedural Techniques For Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…The occurrence of VSD following septal myectomy is rare with reported incidence between 0% and 2%. [ 1 ] In these patients, the ventricular septal tissue quality might be poor due to purposeful prior resection and patch repair could be challenging. Peripheral accessed percutaneous VSD closure is a viable alternative to surgery.…”
Section: Introductionmentioning
confidence: 99%